Occurrence and Antimicrobial Resistance Pattern of Listeria monocytogenes Isolated From Bovine’s Milk and Meat in Mekelle City, Ethiopia - Tesfay Hailu; Getachew Gugsa; Yisehak Tsegaye; Meselu Ahmed; Nesibu Awol (Advances in Public Health)
Listeria monocytogenes is an opportunistic and emerging foodborne zoonotic pathogen that encompasses a diversity of strains with varied virulence and can cause serious human and animal infections worldwide. However, in Mekelle City, the actual prevalence and the antimicrobial susceptibility pattern of L. monocytogenes were not done. Hence, this cross-sectional study was conducted from December 2016 to June 2017 to determine the prevalence of L. monocytogenes and its serotypes and antimicrobial resistance pattern of isolates in Mekelle City, Ethiopia. A total of 768 (n = 384 of milk and n = 384 meat) samples of bovine origin were collected using a purposive random sampling technique. Isolation and identification of L. monocytogenes were done according to standard and recommended bacteriological procedures. Polymerase chain reaction (PCR) amplification of Iap, Imo0737, ORF2819, and ORF2110 genes was performed. In vitro antimicrobial susceptibility testing was performed using agar disk diffusion method. The overall prevalence of L. monocytogenes was 3.39%. The prevalence rates of L. monocytogenes were 4.17% and 2.6% in meat and milk samples, respectively. There was a statistically significant difference (p <0.05) in the prevalence rates of the organism in meat samples collected from abattoir (1.67%), butcher shops (8.33%), and restaurants (8.33%). Serovars that were identified belonged to 1/2b and 4b. Large proportions of isolates were highly susceptible to ampicillin (88.46%) and vancomycin (84.62%). However, the isolates had shown the highest level of resistance against nalidixic acid (96.15%). Moreover, 42.31% of the isolates developed multidrug resistance. Hence, both its occurrence and development of a multidrug resistance indicated the need to practice adequate cocking of bovine origin foods before consumption and rational use of antimicrobials both in veterinary and human treatment regimens with regular surveillance of antimicrobial resistance to combat multidrug resistance.